The medico-legal evaluation of injuries from falls in pediatric age groups - Kafadar, Safiye; Kafadar, Huseyin (Elsevier Sci Ltd, 2015)
Blunt trauma from accidental falls or intentional jumping from great heights occurs frequently in forensic medicine. The goal of this study was to investigate injuries due to falls in children under 19 years of age. Injuries from falls are the leading cause of visits to emergency departments and to deaths due to injuries. Various methods are used in the classification of falls. In this study, we have classified falls as high-level (>= 5 m), low-level (< 5 m) and ground-level. We have retrospectively evaluated 814 boys (61.18%) and 512 girls (38.62%), making up a total of 1326 children (under 19 years old) with the mean age of 7.85 +/- 3.46, that were admitted to State Hospital between January 2009 and December 2013 due to falls from heights and falls on ground-level. Falls were low-level in 738 cases, high-level in 176 cases, and ground-level in 412 cases. Cases were categorized by gender, age, age group, fall height, Glasgow Coma Scale (GCS), injured body part(s), mortality rate, and distribution according to months. In conclusion, falls merit attention because of their high risk of mortality and morbidity, as well as their burden on medical budgets. If the medico-legal aspects of falls were evaluated with regard to preventive event or death, the importance of the topic could be better understood. (C) 2015 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: Falling; Height; Forensic medicine